Equity and efficiency priorities within the Spanish health system: a discrete choice experiment eliciting stakeholders preferences - Mentzakis, E.; García-Goñi, M.; Sequeira, A.; Paolucci, F. (Health Policy and Technology, 2019)
Background The trade-off between efficiency and equity has been largely studied in the health economics literature and for countries with different types of health systems. Even if efficiency and equity are desired, it is not always feasible to attain both simultaneously. In Spain, the National Health System has historically been recognized for its universal access and free of charge provision, with good health outcomes. However, the recent increase in health expenditures together with the economic cycle has turned the orientation of health policy implementation towards efficiency, threatening universality and equity in the access to healthcare. Methods A Discrete Choice Experiment was carried out to weigh priorities of policy-makers from different regions in Spain. A total of 69 valid questionnaires were collected and the preferences towards equity and/or efficiency criteria were evaluated. Composite League Tables (CLTs) were used to rank hypothetical health interventions based on their attributes. Results The Spanish health policy-makers, managers and other stakeholder displayed a stronger preference for severity of disease, high individual benefits, a large number of beneficiaries and proven cost-effectiveness criteria in decision making. The priority interventions targeted severe mental disorders, i.e. major depressive disorders and suicides (or suicidal attempts), especially for young and middle age categories across the three regions under study. Conclusion In times of economic crisis, health policy-makers, managers and other stakeholder value, in moderation, efficiency over equity. The impact of austerity measures on populations’ socio-economic wellbeing seems correlated with the preference for mental health interventions.